2023
DOI: 10.47836/pjtas.46.2.02
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Music on Milk Production and Behaviour of Dairy Cattle

Abstract: The influence of music on the milk performance of dairy cattle has been increasingly studied in recent years, although its efficacy is still being debated due to the inconsistent outcomes and a limited number of studies. This study aimed to investigate the impact of music on the milk production and behaviour of 24 lactating Jersey cattle, consisting of 10 primiparous and 14 multiparous cows. The experiment involved milk collection and behavioural observation before and after exposure to music at a dairy farm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Jiajia et al [63] found that mellow light music (at 70 bpm) improved lactation (nutrient intake and milk yield) performance in Holstein cows. In contrast, Shamshul and Yusof (2023) [64] concluded that music did not improve the milk yield of Jersey dairy cows when cows were exposed to a single playlist (Clayderman's classical piano and Mozart's classical music) maintained at a sound pressure level below 85 dB and frequencies ranging between 23 and 35 kHz. Likewise, Kıyıcı et al [65] did not find significant differences in milk yield in Holstein Friesian cattle exposed to classical music (10.87 ± 0.18 L) and control cows (10.83 ± 0.20 L).…”
Section: Auditory Stimulation In Dairy Cowsmentioning
confidence: 96%
“…Jiajia et al [63] found that mellow light music (at 70 bpm) improved lactation (nutrient intake and milk yield) performance in Holstein cows. In contrast, Shamshul and Yusof (2023) [64] concluded that music did not improve the milk yield of Jersey dairy cows when cows were exposed to a single playlist (Clayderman's classical piano and Mozart's classical music) maintained at a sound pressure level below 85 dB and frequencies ranging between 23 and 35 kHz. Likewise, Kıyıcı et al [65] did not find significant differences in milk yield in Holstein Friesian cattle exposed to classical music (10.87 ± 0.18 L) and control cows (10.83 ± 0.20 L).…”
Section: Auditory Stimulation In Dairy Cowsmentioning
confidence: 96%